2003
DOI: 10.1038/sj.bjc.6601163
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei to detect in vivo chemotherapy damage in a p53 mutated solid tumour

Abstract: Apoptosis induction and micronuclei formation were compared following cytotoxic treatments in two rat glioma differing in p53 integrity. In vitro, micronuclei emergence but not apoptosis was linked to the p53 mutated status. In vivo, micronuclei assays were more sensitive to evaluate DNA damage induced by chemotherapy in a p53-mutated solid tumour. (Mow et al, 2001). The product of the tumour-suppressor gene p53 is a key mediator in this process (Soussi, 2000). In normal cells, wild-type p53 either arrests ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…36 In some studies, apoptosis has been demonstrated to occur weeks after cisplatin treatment. [37][38][39] In such experiments, it is not clear whether apoptosis is due to cisplatininduced signaling events or merely a passive effect [i.e., whether apoptosis is the primary cell death mechanism induced by druginduced signaling, or is a secondary effect induced by lethal cell damage (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…36 In some studies, apoptosis has been demonstrated to occur weeks after cisplatin treatment. [37][38][39] In such experiments, it is not clear whether apoptosis is due to cisplatininduced signaling events or merely a passive effect [i.e., whether apoptosis is the primary cell death mechanism induced by druginduced signaling, or is a secondary effect induced by lethal cell damage (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued that the assessment of micronucleation (which would indicate mitotic catastrophe) can yield a more accurate picture of cell death induction in vivo than the quantitation of apoptosis (Driessens et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For in vitro induction of apoptosis, 9L or 9LmGM-CSF cells were either ␥-irradiated (80 Gy, 137 Cs irradiator) or treated for 2 hours with chemotherapeutic agents (cisplatin at 3 g/mL and mitomycin C at 1 g/mL) before being washed in complete medium and recultured for another 24 or 72 hours. Apoptosis induction was tested by measurement of caspase-3 activation and phosphatidylserine translocation as described previously (26). For in vitro induction of necrosis, 9L or 9LmGM-CSF cells were submitted to one cycle of freeze/thaw, which allows the killing of cells while keeping cell membrane integrity (27).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo detection of apoptosis within 9LmGM-CSF tumors was done by two independent tests: (1) terminal deoxynucleotidyl transferase (Tdt)-mediated nick end labeling (TUNEL) assay, where 9L and 9LmGM-CSF tumors were excised from rats and processed for TUNEL assays as described previously (26); and (2) in situ detection of activated caspase-3, where fixed tissue sections from ex vivo resected tumors were first permeabilized by incubation in PBS-0.2% Triton X-100 for 5 minutes. Nonspecific binding was blocked by 2 hours incubation in PBS-0.1% Tween 20% supplemented with 5% horse serum.…”
Section: Introductionmentioning
confidence: 99%